ALGORITHMS FOR CALCULATING EQUILIBRIUM IN SOLUTIONS OF WEAK ELECTROLYTES - SUPRUNCHUK, VOLODYMYR; IVANYUK, OLENA (Herald of Khmelnytskyi National University. Technical sciences, 2025)
Technological processes based on the use of aqueous solutions of weak electrolytes require justification of technological regimes, where the ionic-molecular composition of solutions is a factor that determines the rational regime of the process. The applied problem and the main in algorithm for calculating the ionic-molecular composition is the use of the values of the ionization constants of weak acids and bases, which are given in the reference and periodic scientific and technical literature. The calculation algorithms presented in the article are based on the following conditions: the condition of equilibrium in solutions, which is actually a condition for the existence of ionization constants of weak acids and bases; the condition of balance over the central atom (this is the atom that determines the main properties of the substance, for example, for phosphoric acid this is the phosphorus atom P); the condition of balance over the hydrogen (hydroxonium) ion. Using the proposed conditions and modeling of equilibrium processes in solutions of weak electrolytes, formulas were derived for calculating the ionic-molecular composition of solutions of weak mono- and polybasic acids and mono- and polyacidic bases. -the equilibrium condition is the basis for the development of calculation algorithms; - the balance condition for the central atom provides and justifies the calculation of the equilibrium molar concentration of particles of different protonation for weak acids and different acidity for base solutions at a forcibly set and controlled pH or pOH value. It is shown that the use of a general approach in the developed calculation algorithm allows deriving formulas for determining equilibrium concentrations for systems of any ionic composition, which simplifies the implementation and regulation of modes when carrying out any technological process in chemical technology.